Penerapan Pendekatan Struktural Think-Pair-Share (TPS) dalam Upaya Peningkatan Hasil Belajar dan Aktivitas Siswa SMA Negeri 1 Tellu Limpoe - Akmal, . (bionature, 2010)
This research was a Classroom Action Research which intended to know  whether  the application of Structural   Think Pair Share (TPS) approach could improve the activitity and study result of the students of X-C  at SMA Negeri 1 Tellu Limpoe Kabupaten Sidenreng Rappang. The subjects of the research were 38 students of SMA Negeri 1 Tellu Limpoe Kabupaten Sidenreng Rappang  which consist of 24 female  and 14 male. The outcomes showed that the application of Structural Think Pair Approach was able to improve  the activity and the study result of tha students. The achievement average of the students was 78,72% with 94,73% as the complete score. Besides ,  there was also improvement to 68,6% of the students activity.